2007
DOI: 10.1038/sj.onc.1210951
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein C-1 maintains cell survival by preventing from apoptosis in pancreatic cancer cells

Abstract: Pancreatic cancer still remains one of the most lethal diseases and establishment of new therapy is needed. The purpose of this study is to find novel factors involved in pancreatic cancer progression by proteomic approach. We compared pre-and postoperative serum protein profiling obtained from pancreatic cancer patients who had curative pancreatectomy using surface-enhanced laser desorption ionization time-of-flight mass spectrometry. The peak intensity levels of both 6630 and 6420 Da were significantly highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
85
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(91 citation statements)
references
References 29 publications
6
85
0
Order By: Relevance
“…Remarkably, in our pilot experiment, apoC-I and apoC-I mimetic peptides enhanced growth of MDA-MB-231 cell cultures representing a 'triple -negative' breast cancer cell line subtype that is aggressive and has few treatment options, promoted proliferation in vitro and improved tumor growth in a MDA-MB-231 xenograft nude mouse model in vivo, in contrast to the MCF-7 (non-TNBC) cell line (data not shown). These data not only support the potential of apoC-I as a biomarker but also its therapeutic utility in TNBC, consistent with the viewpoint of Takano et al 70 Further studies to determine whether apoC-I is secreted from TNBC cells and the molecular mechanisms underlying apoC-I-mediated inhibition of apoptosis in TNBC cells are warranted.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Remarkably, in our pilot experiment, apoC-I and apoC-I mimetic peptides enhanced growth of MDA-MB-231 cell cultures representing a 'triple -negative' breast cancer cell line subtype that is aggressive and has few treatment options, promoted proliferation in vitro and improved tumor growth in a MDA-MB-231 xenograft nude mouse model in vivo, in contrast to the MCF-7 (non-TNBC) cell line (data not shown). These data not only support the potential of apoC-I as a biomarker but also its therapeutic utility in TNBC, consistent with the viewpoint of Takano et al 70 Further studies to determine whether apoC-I is secreted from TNBC cells and the molecular mechanisms underlying apoC-I-mediated inhibition of apoptosis in TNBC cells are warranted.…”
Section: Discussionsupporting
confidence: 69%
“…67,68 An earlier study by Moore and colleagues provided evidence that common functional variations at the APOC1 gene locus increase susceptibility to renal cell carcinoma. 69 Takano et al 70 compared preand postoperative serum protein profiles obtained from pancreatic cancer patients subjected to curative pancreatectomy using SELDI-TOF-MS, and identified 6420 and 6630 Da proteins as apoC-I, which correlated with poor prognosis. These results are relatable to our current findings.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that knockdown of APOC1 expression inhibited cell proliferation, arrested the cell cycle at G 2 /M phase, and promoted apoptosis in DU145 PCa cells in vitro. Similarly, Takano et al 23. showed that inhibition of APOC1 expression suppressed cell survival and induced apoptosis in pancreatic cancer.…”
Section: Discussionmentioning
confidence: 90%
“…Recent studies have shown that APOC1 may be associated with the development of breast cancer, pancreatic cancer, and lung cancer15, 22, 23; however, the role of APOC1 in PCa has not been reported. Accordingly, in this study, we knocked down APOC1 expression in PCa cell lines using RNA interference (RNAi) technology and then explored the effects of APOC1 on PCa in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…6 Using this technology, novel diagnostic markers for alcohol abuse, and also a new prognostic marker for pancreatic cancer have been detected and identified. 7, 8 Although SELDI-TOF MS can rapidly analyze many samples at a time, it has several drawbacks, including high cost, and difficulty in further protein identification.…”
mentioning
confidence: 99%